Interpersonal Relationships Profile of X Graders in Vocational High School - Anggara, Nia; Rusmana, Nandang (International Journal of Applied Guidance and Counseling, 2025)
Interpersonal relationships are a crucial aspect of adolescents' social and emotional development, directly impacting their personal well-being and academic achievement. This study aims to analyze the interpersonal relationship profile of students in Vocational High School. Data were collected from 37 students in Vocational High School and analyzed using descriptive statistics and ANOVA to evaluate the quality of their interpersonal relationships and participation in social activities. Descriptive analysis results indicate that the average quality of students' interpersonal relationships falls in the medium category, with a mean score of 161.378 and a standard deviation of 14.326. Student participation in interpersonal activities is also in the medium category, with a mean score of 42.784 and a standard deviation of 4.510. When both aspects are combined, the overall score for interpersonal relationships is 204.162, with a standard deviation of 17.420. ANOVA analysis shows no significant differences in the quality of interpersonal relationships based on personality types (introvert, extrovert, and ambivert), with a p-value of 0.351. This suggests that personality type does not significantly influence the quality of interpersonal relationships among students at Vocational High School.